TINJAUAN HUKUM NILAI GANTI RUGI DALAM RANGKA PENGADAAN TANAH UNTUK KEPENTINGAN UMUM BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2012 - SUPRIJANTO, AGUS ([Yogyakarta] : Universitas Gadjah Mada, 2015)
professionally and to the recipient of the compensation does not reduce to degree of life, so that the community or the beneficiary compensation after his release can live more feasible in the following. The research is normative emperical means that study is based on secondary research and primery data, secondary data obtained through library research and primery data through field research conducted by interview which to obtain secondary data was done by study document the result of this secondary n qualitative analysis. The result of this research based on how to know that : (1). Equation of the understanding of the compensation in the set by the appraiser value the land is really that in accordance what is desired by the recipient of compensation adjusted by Presidential Regulation No. 71 0f 2012. (2). If the compensation value is not accepted by the receiving party compensation then the only step by compensation beneficiary filed a law suit to court.